Avaliação da influência da energia de soldagem e da adição de arame frio em soldas SAW com arames geminados em aços inoxidáveis lean duplex UNS S32304 - Ronaldo Cardoso Juniotr (2018)
The welding thermal cycle can impair the properties of duplex stainless steels (DSS). Thus, the maximum heat input (HI) recommended for the DSS 2304 is 2.5 kJ/mm, which is a limiting factor for productivity increasing. The addition of cold wire represents an interesting alternative to this issue. The influence of heat input and the cold wire addition (AF) on the chemical, metallurgical, mechanical and corrosion characteristics of SAW welds using the ER2209 filler metal in lean duplex steel UNS S32304 was investigated. ICETM system was used to add a cold wire between two energized twin wires. Bead on plate specimens were produced using heat inputs (1.6, 1.9, 2.2 and 2.7kJ/mm) and the percentage of cold wire was varied in relation to the energized WFS at 0, 50 and 100%. In addition, all weld metal specimens were made and a butt weld joint was produced for the condition considered to be the most critical 2.7 kJ/mm and 100% AF. The thermal cooling cycle was recorded for the extremes heat inputs. For characterization, it was performed chemical analysis, macrography, dimensional analysis, optical microscopy, MEV/EDS, hardness, cyclic potentiodynamic polarization, potentiodynamic polarization with Tafel extrapolation and tensile and Charpy V as mechanical tests. Increasing HI increased cooling time and the increase of AF subtly reduced Ät12/9 and increased Ät9/5. The addition of cold wire reduced the dilution and the loss of the alloying elements during welding, producing welds with higher PREN in the FZ. The addition of cold wire increased the deposition rate by up to 40%, which leads to productivity gains. The microstructure of FZ and HAZ presented GBA, WA, IGA dispersed in the ferritic matrix. Chromium nitride precipitation was observed in HTHAZ ferrite of all welds. The heat input followed the expected behavior, increasing the austenite fraction in the FZ and HAZ and the HTHAZ width. The addition of cold wire significantly affected the ZF, increasing the austenite fraction and the ferrite PREN, but a clear impact of AF on the ZTA microstructure was not noticed. The pitting spots occurred preferentially in the HTHAZ attacking the ferrite, suggesting that pitting corrosion was determined by low PREN and the precipitation of chromium nitrides in the ferrite. Pitting potential was affected by heat input, reducing up to 2.2 kJ/mm and then recovering for 2.7 kJ/mm. AF did not clearly affect HAZ's pitting potential. However, the addition of cold wire significantly reduced the FZ corrosion rate (in mm/year), improving the uniform corrosion. It was possible to produce high productivity welds with satisfactory corrosion resistance and mechanical properties using a heat input higher than the recommended by the literature, of 2.5 kJ/mm, using high cold wire addition, which suggests that this energy value is conservative and can be extrapolated.